KROATISCHE SPRICHWÖRTER IM TEST - Aleksa Varga, Melita; Matovac, Darko (Proverbium - Yearbook, 2016)
The present paper discusses the results of a vast survey conducted in Croatia, in which Croatian proverbs were tested. The list of 105 proverbs included in the questionnaire was compiled in several steps and filtered according to previous research done in the field. The questionnaire was filled out by 867 informants from every major Croatian region, aged from 14 to 87. Although there are also different possibilities and methods to gather information about the familiarity and usage of proverbs, we opted to test the familiarity of proverbs by asking the informants to fill out the first logical half of it. The present paper therefore discusses the results of the survey analysed according to gender, age, and educational degree of the informants.